The SNM1/Pso2 family of ICL repair nucleases: from yeast to man. - Cattell, E; Sengerová, B; McHugh, P (2010)
Efficient interstrand crosslink (ICL) repair in yeast depends on the Pso2/Snm1 protein. Pso2 is a member of the highly conserved metallo-beta-lactamase structural family of nucleases. Mammalian cells possess three SNM1/Pso2 related proteins, SNM1A, SNM1B/Apollo, and SNM1C/Artemis. Evidence that SNM1A and SNM1B contribute to ICL repair is mounting, whereas Artemis appears to primarily contribute to non-ICL repair pathways, particularly some double-strand break repair events. Yeast Pso2 and all three mammalian SNM1-family proteins have been shown to possess nuclease activity. Here, we review the biochemical, genetic, and cellular evidence for the SNM1 family as DNA repair factors, focusing on ICL repair.